Contribution of Local Content Learning in Preserving Kajang Tribe Culture : Phenomenological Study - Kadir, Irsan; Kaharuddin, Kaharuddin; Firdaus, Firdaus; Sari, Nurindah (Universitas Pendidikan Mandalika, 2024)
This research aims to accumulate the concept of formal education in encouraging and maintaining the existence of the Kajang tribe's cultural traditions. The research approach used is a qualitative with a phenomenological method. The informants in this study were the Kajang tribal leaders, the community, parents of students, and teachers of SDN 351 Kawasan Amma Toa. Data collection techniques used were through observation, interviews and documents. The data obtained were then analyzed through three stages, namely data reduction, data presentation and drawing conclusions. The results of the research show that